Internet Addiction Correlates with Sleep Quality in Adolescents - Elfa Dhela Miranda; Bayu Nirwana; Agni Bunga Saafitri (Journal Keperawatan, 2026)
Background: The rapid development of the internet has made it easier for teenagers to obtain information, communicate, play games, and use social media. High levels of internet use can increase the risk of internet addiction in adolescents. Good quality sleep is essential for cognitive function, concentration, academic achievement, and physical and mental health. Late-night internet use, coupled with difficulty controlling the duration of use, can potentially lead to changes in sleep patterns in adolescents. Purpose: To determine the relationship between internet addiction and sleep quality in adolescents at MAN 1 Subang. Methods: This study used a quantitative method with a cross-sectional design. The study population consisted of 781 students at MAN 1 Subang, using proportionate stratified random sampling technique and a sample size of 89 respondents. The instruments used were the Internet Addiction Test (IAT) questionnaire to measure internet addiction levels and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. Results: A total of 46 adolescents (51.7%) experienced moderate internet addiction, while 83 adolescents (93.3%) had poor sleep quality. Spearman's correlation test results showed a significant positive relationship with weak strength between internet addiction and sleep quality in adolescents (rₛ = 0.224; p = 0.035). Conclusion: Internet addiction is significantly associated with sleep quality in adolescents, although the strength of the relationship is weak. Higher levels of internet addiction tend to be associated with poorer sleep quality. Education on wise internet use and time management is needed to support adolescent sleep quality.